OPTIMASI METODE C4.5 MENGGUNAKAN ALGORITMA GENETIKA UNTUK KLASIFIKASI STUDI LANJUT SISWA MADRASAH - ; A. Zulham F.H (Program Studi Teknik Informatika, Fakultas Teknik, Universitas Yudharta Pasuruan)
Students (learners) are children or adolescents who get science education, guidance, and direction so as to get changes, developments in shaping a personality, as well as a structural education in the teaching process. In Permendikbud No. 5 of 2015 article 4 also explained the value of report cards must be 50% to 70% and the value of UN weighted between 30%. So in this research will do classification of advanced study of madrasah students by using algorithm C4.5 which has the highest level of accuracy, but in this research will be conducted optimization of assessment using genetic algorithm to mendaptkan better result. The process within the genetic algorithm is used to obtain an optimal solution of rapid value for complex problems in determining the value of subjects for five semesters. In experiments on the Decision Tree (C4.5) and Decision Tree algorithms coupled with optimizations using Genetic Algorithm (GA). From both tests it can be seen that Decision Tree (C4.5) research resulted Accuracy 79,43%, while Decision Tree (C4.5) with Genetic Algorithm (GA) as feature selection resulted Accuracy 81,43%.